Explorations in Reconciliation New Directions in Theology - Tombs, David; Liechty, Joseph (Taylor & Francis, 2006)
Theologians and scholars of religion draw on rich resources to address the complex issues raised by political reconciliation in the Middle East, the former Yugoslavia, South Africa, Northern Ireland and elsewhere. The questions addressed include: Can truth set a person, or a society, free? How is political forgiveness possible? Are political, personal, and spiritual reconciliation essentially related? Explorations in Reconciliation brings Catholic, Protestant, Mennonite, Jewish and Islamic perspectives together within a single volume to present some of the most relevant theological work today. The Open Access version of this book, available at http://www.taylorfrancis.com/books/e/ISBN, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. The support of the Irish School of Ecumenics Trust in making this OA version possible is gratefully acknowledged.